Prevelance and associations of myelinated retinal nerve fibers: results from the population-based Gutenberg health study - El-Baz, Hisham; Mirshahi, Alireza (Retina, 2016)
Purpose: To determine the prevalence, ocular, and systemic associations of myelinated retinal nerve fibers (MRNF) in a Caucasian cohort. - Methods: The Gutenberg Health Study (GHS) is a population-based, prospective cohort study encompassing 15,010 subjects in Germany. Gutenberg Health Study participants, aged 35 to 74 years, stratified for gender, decades of age, and residence were examined for ophthalmologic and systemic conditions. Optic disc centered and macular photographs were reviewed for the presence of MRNF. - Results: In 25,728 eyes of 12,906 participants (86.0% of the cohort), the prevalence of MRNF was 0.4%. In a binary logistic regression analysis, MRNF was positively associated with history of stroke (OR, 6.8; 95% CI, 2.9-16.1; P < 0.001). Myelinated retinal nerve fibers was not associated with age, sex, cardiovascular conditions other than stroke or ocular parameters, such as refraction, visual acuity, intraocular pressure, or central corneal thickness. - Conclusion: This population-based study provides novel data on the prevalence of MRNF in Western Europe. We report a positive association between history of stroke and MRNF. It adds an additional retinal sign for stroke and calls for further studying of the behavior of oligodendrocytes within cerebrovascular diseases.
Gesehen am 30.10.2019